2020
DOI: 10.1186/s12885-020-07657-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a four-gene panel predicting overall survival for lung adenocarcinoma

Abstract: Background Lung cancer is the most frequently diagnosed carcinoma and the leading cause of cancer-related mortality. Although molecular targeted therapy and immunotherapy have made great progress, the overall survival (OS) is still poor due to a lack of accurate and available prognostic biomarkers. Therefore, in this study we aimed to establish a multiple-gene panel predicting OS for lung adenocarcinoma. Methods We obtained the mRNA expression and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Therefore, with the development of bioinformatics, an increasing number of novel biomarkers have been constructed to get involved in the diagnosis and prediction of cancer [ 28 , 29 ]. These signatures are associated with metabolism [ 30 ], immune [ 31 ], and DNA methylation [ 32 ]. The standards to judge the model are convenient, credible, and precise.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, with the development of bioinformatics, an increasing number of novel biomarkers have been constructed to get involved in the diagnosis and prediction of cancer [ 28 , 29 ]. These signatures are associated with metabolism [ 30 ], immune [ 31 ], and DNA methylation [ 32 ]. The standards to judge the model are convenient, credible, and precise.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the predictive value of gene expression for the prognosis of patients suffering from cancer, including breast, colorectal, lung, gastric, and ovarian cancer (Li et al, 2020a;Pei et al, 2020;Xie et al, 2020;Zhang et al, 2020b). Most of these studies involved the selection of differentially expressed genes followed by the screening of prognosis-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Gene sequencing has developed rapidly over the last few years and has allowed us to identify an increasing number of molecular prognostic factors for several cancers, including colon cancer, lung cancer, and breast cancer (Pei et al, 2020;Yang et al, 2020;Zhang et al, 2020a). Indeed, recent studies have demonstrated that genomic data are superior to the traditional staging system for estimating the risk of a worse prognosis and predicting the benefit of adjuvant chemotherapy (He & Zuo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an increasing number of novel biomarkers have been constructed to involve in the diagnosis and prediction on cancer with the development of bioinformatics. These signatures are associated with metabolism [24], immune [25], DNA methylation [26]. The standards to judge the model are whether it is convenient, credible, and precise.…”
Section: Discussionmentioning
confidence: 99%